Nursing Care in Healthcare-Associated Infections: A Scoping Review - Ferreira,Larissa de Lima (2019)
ABSTRACT Objective: To identify and map nursing care to the adult patient with Healthcare-Associated Infections admitted to the Intensive Care Unit. Method: Scoping Review, conducted in January 2018, through the search of studies in national and international databases, journals, catalogs of theses and dissertations, and websites of Brazilian health institutions. We included full surveys published in the Portuguese, Spanish or English language; which had as object of study the researched subject, besides manuals and protocols. We analyzed the type of material, year, country, population, method, Level of Evidence, and nursing care. The final sample consisted of 33 publications. Results: Among the nursing care to the patient, hand hygiene was identified, general care in nursing procedures, use of protocols, effective communication and periodic training. Conclusion: Identifying patient care with infection was important in order to list methods and reorient nursing activities.